Are receptor-associated nuclear proteins associated with the earliest effects of steroid hormones? (Revista Española de Fisiología, 1990)
The functional importance of the interaction of hsp90 with receptors for steroid hormones in the action of these hormones has been suggested. This hypothesis, although not yet proven, is supported by new data obtained in our laboratory and in those of others, whereas no conflicting experimental results have been presented. Our recent studies have dealt with the cloning of hsp90, transfection of normal and mutated receptors, the effects of the antihormone RU486 and immunohistochemistry.